Reuse of sugarcane bagasse ash (SCBA) to produce ceramic materials - Souza, A. E. [UNESP]; Teixeira, S. R. [UNESP]; Santos, G. T. A. [UNESP]; Costa, F. B. [UNESP]; Longo, Elson [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2011)
Sugarcane bagasse ash (SCBA) is a residue resulting from the burning of bagasse in boilers in the sugarcane/alcohol industry. SCBA has a very high silica concentration and contains aluminum, iron, alkalis and alkaline earth oxides in smaller amounts. In this work, the properties of sintered ceramic bodies were evaluated based on the concentration of SCBA, which replaced non-plastic material. The ash was mixed (up to 60 wt%) with a clayed raw material that is used to produce roof tiles. Prismatic probes were pressed and sintered at different temperatures (up to 1200 degrees C). Technological tests of ceramic probes showed that the addition of ash has little influence on the ceramic properties up to 1000 C. X-ray diffraction and thermal analysis data showed that, above this temperature the ash participates in the sintering process and in the formation of new important phases. The results reported show that the reuse of SCBA in the ceramic industry is feasible. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Clay; Ash; Sugarcane; Additive; Sintering; Mullite